Joy: The Happiness that Comes from Within - Osho (St. Martin's Griffin, 2004)
The Insights for a New Way of Living series aims to shine light on beliefs and attitudes that prevent individuals from being their true selves. With an artful mix of compassion and humour, Osho encourages his audience to confront what they would most like, to avoid, which in turns provides the key to true insight and power.